2009
DOI: 10.1007/s11357-009-9115-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of old age on apolipoprotein E and its receptors in rat liver

Abstract: Apolipoprotein E (apoE) is associated with aging and some age-related diseases. The majority of apoE is produced by hepatocytes for the receptormediated uptake of lipoproteins. Here, the effects of age on the hepatic expression and distribution of apoE and its receptors were determined using immunofluorescence, Western blots, and quantitative PCR in rat liver tissue and isolated hepatocytes. The expression of apoE mRNA and protein was not influenced significantly by aging. Immunofluorescence studies in isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Cell energy and metabolism, including mitochondrial dysfunction, is one of the top processes ( Campisi et al, 2019 ; Javadov et al, 2020 ; Sprenger and Langer, 2019 ). Proteins such as clusterin, superoxide dismutase 1 (SOD1), and apolipoprotein E have previously been found to be dysregulated in ageing ( Sabaretnam et al, 2010 ; Sentman et al, 2006 ; Trougakos and Gonos, 2006 ). Although we were underpowered to gain significant insights from IPA and DAVID pathway analysis packages, by STRING analysis bone displayed a very strong metabolic, mitochondrial signature, and we found clusterin dysregulation in plasma, cartilage, and bone of older adult mice, and down-regulation of SOD1 in cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Cell energy and metabolism, including mitochondrial dysfunction, is one of the top processes ( Campisi et al, 2019 ; Javadov et al, 2020 ; Sprenger and Langer, 2019 ). Proteins such as clusterin, superoxide dismutase 1 (SOD1), and apolipoprotein E have previously been found to be dysregulated in ageing ( Sabaretnam et al, 2010 ; Sentman et al, 2006 ; Trougakos and Gonos, 2006 ). Although we were underpowered to gain significant insights from IPA and DAVID pathway analysis packages, by STRING analysis bone displayed a very strong metabolic, mitochondrial signature, and we found clusterin dysregulation in plasma, cartilage, and bone of older adult mice, and down-regulation of SOD1 in cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…33 APOE mRNA levels from rat brain and liver did not change with aging. 34,35 Although murine hematopoietic stem cells alter their transcriptomes on aging, 36 there have been no prior reports of transcript changes in normal aging human tissue. We identified 129 mRNAs DE by age but APOE was in the bottom 13th percentile of platelet transcripts and was not DE by age in PRAX1.…”
Section: Effect Of Age On Rna Expressionmentioning
confidence: 99%
“…Cell energy and metabolism, including mitochondrial dysfunction, is one of the top processes (31)(32)(33). Proteins such as clusterin, superoxide dismutase 1(SOD1), and apolipoprotein E have previously been found to be dysregulated in ageing (34)(35)(36). In this study, we found clusterin dysregulation in plasma, cartilage and bone of 45 week old mice when compared with those at 15 weeks of age, and downregulated SOD1 in cartilage.…”
Section: Discussionmentioning
confidence: 59%